Importancia de los macronutrientes en el cultivo de soya (Glycine max) - Macias Quezada, Ana Elizabeth (2019)
Soy is part of one of the largest crops in Ecuador and represents a considerable sector within the country's economy, being a crop that occurs mostly in the Coastal Region. This research has focused on analyzing the importance of macronutrients in the cultivation of soybeans, which are vital for their normal development, so it must have been analyzed one by one, to place them in a relevant degree within the growth structure from the soybean plant. The deficiencies described in this document show their results and are identified according to the analysis of the appearance of the plant, thus determining what macronutrients are needed for the soy plant to develop normally. Finalizing the recommendations, it is proposed to train the farmers to know how to recognize the problems of macronutrient deficiencies in soybean cultivation, and to apply appropriate fertilization programs